DETERMINASI ARAH KIBLAT MENGGUNAKAN AZIMUTH AWAN CUMULONIMBUS (RELEVANSI KAJIAN ILMU FALAK DAN METEOROLOGI) - Fajar, Muh.; Rizal, andi Syam (Universitas Islam Negeri Alauddin Makassar, 2026)
Abstract This study discusses the determination of the direction of the Qibla using the azimuth of the cumulonimbus cloud as an alternative to determining the direction of the Qibla in the perspective of the integration of astronomy and meteorology. This research is motivated by the importance of the direction of the qibla in prayer and the need for alternative methods of determining the direction of the qibla when modern tools or astronomical observations cannot be used optimally. Therefore, this study aims to find out: 1) how to determine the direction of the qibla using the azimuth of the cumulonimbus cloud; 2) How is the accuracy of the azimuth of the cumulonimbus cloud in determining the direction of the Qibla. Cumulonimbus clouds are chosen because they have the characteristics of vertical growth and a specific direction of movement that can be visually observed in the atmosphere. This study uses the library research method with a normative sharia and descriptive approach. Data were obtained through literature reviews in the form of books, journals, scientific articles, and relevant sources that discuss the direction of the qibla, astronomy, meteorology, azimuth, and characteristics of cumulonimbus clouds. The analysis was carried out by examining the relevance between the concept of azimuth in astronomy and the movement pattern of cumulonimbus clouds in meteorology. The results of the study show that the azimuth of cumulonimbus clouds can theoretically be used as an alternative indicator in determining the direction of the qibla, especially when the position of the sun and other celestial bodies cannot be observed directly. However, the accuracy level of this method is influenced by atmospheric conditions, wind direction, cloud stability, and the geographical position of the observer. Therefore, this method cannot replace the main astronomical method, but it can be used as an alternative approach based on natural phenomena. This study shows the relevance between astronomy and meteorology in the development of adaptive and contextual Qibla direction determination methods. The implications in this study need to be positioned as a supporting alternative in the analysis of the falak, while the astronomical method that has a better level of precision, stability, and validity of measurements remains the main foundation in determining the direction of the qibla. Keywords: Qibla Direction, Azimuth, Cumulonimbus Clouds, Islamic Astronomy, Meteorology